Peran Sains Dalam Membangun Kualitas Generasi Islam: Role of Science in Boilding Quality of Islamic Generation - Chumaida Amelia Putri; Siti Nur Hasanah; Alfina Wildatul Fitriyah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Science is always associated with general knowledge or science that studies worldly matters only. Some Muslims think that science has nothing to do with Islam or in other words, Islam does not need science. If the Islamic community's opinion about this still exists then Islam is in a danger zone, because Islam actually needs science. Islam and science are not two opposing camps, but rather two very unified camps. If we look deeper, the Koran presents many verses about science. The verses of the Koran about science range from 750 to 1000 verses. In fact, the first revelation that came down to the Prophet Muhammad SAW was the command to read. In the Qur'an, it is explained that paying attention to the universe, which also means studying science, is part of reading the verses of Allah SWT. Meanwhile, the results of research conducted by scientists about the universe do not contradict the Koran which was revealed 1400 years ago. If science and technology are only controlled by non-Muslims, then Muslims will be considered weaker and inferior in the field of science. Therefore, Islam needs the next generation of people who love and understand the contents of the Koran and are not blind to knowledge, especially science. Islam will spread its wings more in the fields of science and technology so that a generation of Muslims who are IMTAQ and SCIENTIFIC will be formed, namely a generation of Muslims who are faithful and devout and master science and technology.